2211. High prevalence of Chlamydia trachomatis and Neisseria gonorrhoeae identified through routine screening for rectal, pharyngeal, and urethral infections within a HIV pre-exposure prophylaxis program in Hanoi, Vietnam. (15th December 2022) - Adamson, Paul C; Bui, Hao; Pham, Loc; Le, Hai; Nguyen, Trung; Le, Giang; Klausner, Jeffrey
Abstract: Background: Pre-exposure prophylaxis (PrEP) is highly effective for HIV prevention and is being scaled up globally. Patients on PrEP have high rates of bacterial STIs, like Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG), thus routine screening is recommended. However, access to screening tests for STIs are limited in many low-resource settings. The objectives of this study were to determine the prevalence of CT and NG among participants in Vietnam's first PrEP program. Methods: From January through April 2022 participants in the PrEP program at the Sexual Health Promotion Clinic in Hanoi, Vietnam were recruited to study STI prevalence. Study participants completed a survey collecting demographic, behavioral and clinical characteristics. Participants self-collected urine, rectal, and pharyngeal specimens for nucleic-acid testing. Participants positive for NG had an additional specimen collected for culture and antibiotic susceptibility. Results: In total, 108 participants were enrolled, median age was 24 years (IQR: 22– 28). All were male and reported having sex with men in the prior 12 months. The median number of sex partners in the prior 1 month was 1 (IQR: 1 – 2). Symptoms within the prior week were reported by 41.7% (45/108) – 19.4% reported rectal, 15.7% reported urethral, and 26.9% reported pharyngeal symptoms. The overall prevalence of CT or NG infections was 31.5% (34/108). The prevalence of CT was 24.1% (26/108); by anatomic site, there were 17 (15.7%) rectal, 10 (9.3%) pharyngeal, and 6 (5.6%) urethral infections. The prevalence of NG was 13.0% (14/108); there were 12 (11.1%) pharyngeal, 9 (8.3%) rectal, and 0 urethral infections. Among participants reporting any symptoms, CT prevalence was 26.7% (12/45) and NG prevalence 13.3% (6/45). All infections were treated. Conclusion: The prevalence of CT and NG was very high among this population of young MSM in a PrEP program in Hanoi, Vietnam. A high proportion of CT infections were rectal (65%) and 86% of NG infections were pharyngeal. These findings highlight the need for expanded access to extragenital nucleic-acid testing among PrEP programs in low- and middle-income countries. Studies demonstrating the benefit of CT/NG screening and treatment within PrEP programs are urgently needed. Disclosures: Jeffrey Klausner, MD MPH, Cepheid: Advisor/Consultant|Cepheid: Grant/Research Support|Cepheid: Research equipment and supplies.